Pregnancy and Delivery Complications Between Adolescent and Adult Women at Mosul Maternity Teaching Hospitals: A Comparative Study - Marwa Ibrahim Shaban, Salwah H. Almukhtar (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Adolescent pregnancy is one of the common public health problems worldwide today, with harmful health effects to the foetus, mother and the neonate. Aims of the study: To identify the demographical characteristics of the study sample and to compare the complications of pregnancy and delivery between adolescent and adult pregnant women and to find out the relationship between demographical characteristics and study variables Patients and Methods: A quantitative cross-sectional observational study design was conducted in four maternity teaching hospitals in Mosul, Iraq, from the 10th of December 2021, until the 1st of March 2022. The study group included 100 pregnant adolescents aged 10–19 years, and the comparable group included 157 pregnant women aged between 20 and 45 years. Result: In comparison to adult women, adolescent women are more likely to suffer from anemia (77%), IUGR (13%), abruptio placenta (15%), psychological problems (24%), cervical insufficiency (20%), preterm labor (26%), obstructed labor (41%), prolonged labor (29%), postdate (30%), neonatal death (6%), and episiotomy (36%). Conclusion: There is a statistically significant difference (p<0.05) between the two groups in terms of anemia, gestational diabetes, urinary tract infection, intrauterine growth restriction, abruptio placenta, psychological problem, incompetence cervix, preterm labour, prolong labour, postdate, obstructed labour, dead newborn, episiotomy, and there is a direct and positive correlation between a husband’s job with H.T and between BMI with (UTI, IUGR, preterm labour, prolonged labor) and between educational level with (abruptio placenta, CPD, postdate) and occupation with abruptio placenta. Recommendation: Instructing the Iraqi courts and the Ministry of Justice to legislate a law prohibiting the adolescent marriage and encourage the Iraqi Ministry of Health to activate family planning programs to delay pregnancy until the young girl’s reach maturity. Keyword: adolescent, pregnancy, delivery, complication, adult